2022
DOI: 10.1097/corr.0000000000002251
|View full text |Cite
|
Sign up to set email alerts
|

Halicin Is Effective Against Staphylococcus aureus Biofilms In Vitro

Abstract: BackgroundBiofilms protect bacteria from the host immune system and many antibiotics, making the treatment of orthopaedic infections difficult. Halicin, a recently discovered antibiotic, has potent activity against nonorthopaedic infections in mice and the planktonic, free-living forms of many bacterial species, including Staphylococcus aureus, a common cause of orthopaedic infections. Importantly, halicin did not induce resistance in vitro and was effective against drug-resistant bacteria and proliferating an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Investigators from Indianapolis (Indiana, USA) therefore sought to test the effectiveness of halicin against biofilms in vitro. 1…”
Section: Halicin Effective Against Staphylococcus Aureus Biofilms In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Investigators from Indianapolis (Indiana, USA) therefore sought to test the effectiveness of halicin against biofilms in vitro. 1…”
Section: Halicin Effective Against Staphylococcus Aureus Biofilms In ...mentioning
confidence: 99%
“…Investigators from Indianapolis (Indiana, USA) therefore sought to test the effectiveness of halicin against biofilms in vitro. 1 Biofilms were exposed to various concentrations of halicin, tobramycin, cefazolin, vancomycin, or rifampicin for 20 hours, with biofilm viability determined by measuring resazurin reduction or by counting colony-forming units after sonication. The investigators found no differences between halicin’s effectiveness against planktonic S. aureus and three-day biofilms, although the drug was eight-fold less effective against seven-day biofilms.…”
Section: Halicin Effective Against Staphylococcus Aureus Biofilms In ...mentioning
confidence: 99%
“…The authors of this study [5] tested a new antimicrobial agent, halicin, on the biofilms of the S. aureus strain Xen36 and compared its efficacy with the efficacy of other commonly used antibiotics such as tobramycin, cefazolin, vancomycin, and rifampicin. The model used planktonic cells and 3-day- and 7-day-old biofilms.…”
Section: Where Are We Now?mentioning
confidence: 99%
“…Halicin has garnered substantial attention in recent years because of its potential therapeutic applications. As a potential broad-spectrum antibacterial agent, halicin showed remarkable efficacy against both Gram-positive and Gram-negative bacteria ( Stokes et al, 2020 ; Booq et al, 2021 ; Higashihira et al, 2022 ). Halicin has a lower likelihood of inducing bacterial resistance than traditional antibiotics.…”
Section: Introductionmentioning
confidence: 99%